Polymorphisms in Inflammatory Mediator Genes and Risk of Preeclampsia in Taiyuan, China - Wu, Weiwei (Reprod Sci, 2016)
Excessive maternal inflammatory response is involved in the pathogenesis of preeclampsia. Few epidemiologic studies have investigated the associations between genetic variations in the inflammatory mediator genes and preeclampsia risk, and these studies have reached inconsistent results. We examined 31 single-nucleotide polymorphisms in IL-1A, IL-1B, IL-1R1, IL-2RA, IL-5RA, IL-6, IL-6R, TNFSF11, TNFRSF11A, IL-28RA, IRAK4, and KIT genes and the risk of preeclampsia and its clinical subtypes in a nested case–control study including 203 preeclampsia cases and 233 controls. We found that IL-1R1, IL-5RA, IL-6R, and TNFSF11 were associated with the risk of preeclampsia. Although the significant associations observed for preeclampsia overall were mainly seen for late-onset preeclampsia and severe preeclampsia, IL-6R (rs2229238) and TNFSF11 (rs9525643) polymorphisms were associated with the risk of early-onset preeclampsia. TNFSF11 (rs2200287 and rs2148072) polymorphisms were associated with risk of mild preeclampsia. Our study provided the first evidence that genetic variations in inflammatory mediator genes IL-1R1, IL-6R, TNFSF11, and IL-5RA were associated with preeclampsia risk, and the risk varied by preeclampsia subtypes.